Pengaruh Boikot, Brand Awareness dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Produk Lokal di Kota Batam - Sulistio Prayoga Sinaga; Suhardi Suhardi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study focuses on identifying the influence of Boycott, Brand Awareness, and Consumer Trust on the Purchase Decision of Local Product in Batam City, both partially and simultaneously. The research aims to examine the effect of boycott, brand awareness, and consumer trust on the purchase decision of Sanford mineral water in Batam City. This study adopts a quantitative approach, involving a sample of 100 respondents, with data collected through the distribution of questionnaires. The results indicate that the variables of Boycott, Brand Awareness, and Consumer Trust have a positive and significant effect-both individually and collectively-on the purchase decision of Sanford mineral water